2020
DOI: 10.3389/fcell.2020.00845
|View full text |Cite
|
Sign up to set email alerts
|

Tethering of Telomeres to the Nuclear Envelope Is Mediated by SUN1-MAJIN and Possibly Promoted by SPDYA-CDK2 During Meiosis

Abstract: During meiosis, telomeres attach to the nuclear envelope (NE) to promote homologous chromosome moving, pairing, synapsis, and recombination. The telomere-NE attachment is mediated by SUN1, TERB1-TERB2-MAJIN (TTM complex), and TRF1. The interaction of the TTM complex with shelterin is mediated by TERB1 and TRF1, but how SUN1 interacts with the TTM complex is not yet fully understood. In this study, we found that SUN1 not only interacted with TERB1 but also interacted with MAJIN, and the interaction of SUN1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In zebrafish, components of the meiotic chromosome axis are assembled immediately adjacent to the telomeres in the leptotene stage (Figure 2G), suggesting that some component of the shelterin complex or meiosis-specific associated proteins, such as Terb1 and Terb2 or Majin may be involved in seeding the initiation of axis biogenesis (de Lange, 2005;Shibuya et al, 2014Shibuya et al, , 2015. In Terb1 −/− , Terb2 −/− , and Majin −/− mice, telomere attachment to the nuclear envelope is disrupted (Daniel et al, 2014;Shibuya et al, 2014Shibuya et al, , 2015Pendlebury et al, 2017;Dunce et al, 2018;Wang et al, 2019Wang et al, , 2020. These proteins are conserved among metazoans, so they likely play a similar role in zebrafish (da Cruz et al, 2020).…”
Section: Telomere Bouquetmentioning
confidence: 99%
“…In zebrafish, components of the meiotic chromosome axis are assembled immediately adjacent to the telomeres in the leptotene stage (Figure 2G), suggesting that some component of the shelterin complex or meiosis-specific associated proteins, such as Terb1 and Terb2 or Majin may be involved in seeding the initiation of axis biogenesis (de Lange, 2005;Shibuya et al, 2014Shibuya et al, , 2015. In Terb1 −/− , Terb2 −/− , and Majin −/− mice, telomere attachment to the nuclear envelope is disrupted (Daniel et al, 2014;Shibuya et al, 2014Shibuya et al, , 2015Pendlebury et al, 2017;Dunce et al, 2018;Wang et al, 2019Wang et al, , 2020. These proteins are conserved among metazoans, so they likely play a similar role in zebrafish (da Cruz et al, 2020).…”
Section: Telomere Bouquetmentioning
confidence: 99%
“…Similarly, in mouse spermatocytes, MAJIN connects the meiosis-specific shelterinbinding proteins TERB1 and TERB2 to LINC complexes (Wang et al, 2020). MJL-1 requires PLK-2 activity to interact with PC proteins, while CDK2 activity is required for interaction between MAJIN and SUN1 in mice (Wang et al, 2020; Mikolcevic et al, 2016; Tu et al, 2017). In fission yeast, a direct interaction between NE proteins Bqt3 and −4 and LINC complexes has not been detected.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear envelope protein complex TERB1/2-MAJIN provides alternative telomere-nuclear membrane attachment during meiosis, suggesting that the telomere-TERB1-TERB2-MAJIN-nuclear envelope associating with the telomere-LINC complex may cooperatively recruit telomeres to the nuclear envelope during meiosis [ 78 , 79 ]. Recent studies have shown that SUN1 interacts with MAJIN and TERB1 [ 80 , 81 ]. Therefore, a possible explanation is that ALT cells might borrow meiotic proteins, such as the TERB1/2-MAJIN complex, to orchestrate telomere attachment during the mitotic cell cycle.…”
Section: Discussionmentioning
confidence: 99%